The false-blister beetles (Coleoptera, Oedemeridae) of Oman with the description of a new species - Poloni, Riccardo (Zootaxa, 2022)
This paper is the first to deal with the false-blister beetle of the sultanate of Oman: it provides an overview of the biogeography of the country and an annotated checklist of the eight known species, four of which are new for Oman. In addition, a new species, Probosca (Proboxantha) coniuncta n. sp. is described.